Do indoor plants improve performance and well-being in offices? Divergent results from laboratory and field studies. (October 2020) - Thatcher, Andrew; Adamson, Kaylin; Bloch, Lara; Kalantzis, Anastasia
Abstract: Laboratory studies, mostly with students as samples, consistently demonstrate the psychological benefits of indoor plants. However, these findings do not always translate into benefits for employees in real work contexts. In three studies, this paper first looked to replicate the findings of previous laboratory studies for the South African context and then to assess whether these findings were robust in two call centre field studies. In the laboratory study, the condition with indoor plants performed statistically better on three measures of work performance. These positive outcomes could not be replicated in two field studies using various proxy measures of performance and wellbeing (perceived productivity, perceived physical and psychological health, work engagement, job satisfaction, and evaluations of the work environment) with varying lengths of exposure to indoor plants (6 weeks in Study 2 and 14 weeks in Study 3). The moderating role of connectedness to nature (Studies 1 and 2) was not supported while the moderating role of attractiveness of the plants (Study 3) was only partially supported in Study 3. These results are discussed in relation to the differences between laboratory and field studies, specifically in the context of call centre agents. Highlights: Performance is higher with office plants and pictures of plants compared to a lean condition in the laboratory study. Performance and wellbeing were unaffected by office plants in two fields studies of call centre environments. Connectedness to nature did not moderate these relationships and perceived attractiveness moderated some relationships. The role of indoor office plants in ameliorating negative impacts of work may be overstated for call centre environments.